Micro and Nano Fabrication Technology (Micro/Nano Technologies,, 2018)
This volume focuses on the state-of-the-art micro/nanofabrication technologies for creating miniature structures with high precision. These multidisciplinary technologies include mechanical, electrical, optical, physical, and chemical methods, as well as hybrid processes, covering subtractive and additive material manufacturing, as well as net-shape manufacturing. The materials the volume deals with include metals, alloys, semiconductors, polymers, crystals, glass, ceramics, composites, and nanomaterials. The volume is composed of 30 chapters, which are grouped into five parts. Engaging with the latest research in the field, these chapters provide important perspectives on key topics, from process developments at the shop level to scientific investigations at the academic level, offering both experimental work and theoretical analysis. Moreover, the content of this volume is highly interdisciplinary in nature, with insights from not only manufacturing technology but also mechanical/material science, optics, physics, chemistry, and more.